Union of the Comoros : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews the Staff-Monitored Program (SMP) for the Union of the Comoros. The authorities' program for 2005 is focused on macroeconomic stabilization. This is predicated on a consolidated budget entailing a domestic fiscal adjustment slightly above 3 percent of GDP. Monetary policy will remain circumscribed by the country's participation in the Franc zone. Agreement in principle was reached on a SMP covering 2005. The program would support the authorities' economic reforms and establish a track record of policy implementation that could lead to a Poverty Reduction and Growth Facility arrangement.